2015
DOI: 10.1371/journal.pone.0119467
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Neurospheres Are Not Specific to Neural Crest Cultures: Implications for Neural Stem Cell Therapies

Abstract: ObjectivesEnteric neural stem cells provide hope of curative treatment for enteric neuropathies. Current protocols for their harvesting from humans focus on the generation of ‘neurospheres’ from cultures of dissociated gut tissue. The study aims to better understand the derivation, generation and composition of enteric neurospheres.DesignGut tissue was obtained from Wnt1-Cre;Rosa26Yfp/Yfp transgenic mice (constitutively labeled neural crest cells) and paediatric patients. Gut cells were cultured either unsorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 49 publications
4
62
0
Order By: Relevance
“…Depending on the individual culture protocols and markers used, NLBs from early postnatal mouse/rat gut are immunoreactive for typical neural differentiation markers after an in vitro culture period up to 2 weeks (Belkind-Gerson et al, 2013; Binder et al, 2015; Bondurand et al, 2003; Dettmann et al, 2014; Kruger et al, 2002; Silva et al, 2008). A small fraction of NLB cells (<15%) remain negative for all differentiation markers used, raising the possibility that at least a subfraction of the isolated cells that generate neurospheres are undifferentiated progenitors or NSCs (Bondurand et al, 2003).…”
Section: How Are “Neurospheres” and The Neural Progenitors Withinmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the individual culture protocols and markers used, NLBs from early postnatal mouse/rat gut are immunoreactive for typical neural differentiation markers after an in vitro culture period up to 2 weeks (Belkind-Gerson et al, 2013; Binder et al, 2015; Bondurand et al, 2003; Dettmann et al, 2014; Kruger et al, 2002; Silva et al, 2008). A small fraction of NLB cells (<15%) remain negative for all differentiation markers used, raising the possibility that at least a subfraction of the isolated cells that generate neurospheres are undifferentiated progenitors or NSCs (Bondurand et al, 2003).…”
Section: How Are “Neurospheres” and The Neural Progenitors Withinmentioning
confidence: 99%
“…Some investigators have attempted to enrich putative fetal and postnatal ENS progenitors using either surface markers such as RET (Binder et al, 2015; Lo and Anderson, 1995; Natarajan et al, 1999), the neurotrophin receptor p75(NTR), α4 integrin (Bixby et al, 2002; Kruger et al, 2002; Mosher et al, 2007; Tsai et al, 2011) or Sox2/Sox10/Nestin promoter-driven reporter genes (Bondurand et al, 2006; Heanue and Pachnis, 2011). Using these approaches only some of the selected cells proliferated and not all proliferating colonies were equally multipotent.…”
Section: How Are “Neurospheres” and The Neural Progenitors Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies have demonstrated successful expansion of ENSCs as enteric “neurospheres.” In theory, dissociated intestinal cells are cultured in the appropriate conditions to allow neural progenitors to proliferate and other cell types to be eliminated spontaneously [13, 45, 46]. However, others have shown that enteric neurospheres consist of a heterogeneous population of cells, including neurons, glial cells, and non-neural crest-derived cells, such as smooth muscle and mesenchymal cells [8, 43]. We analyzed cell composition in our dissociated neurospheres and observed p75-immunoreactivity in up to 25% of cells, Tuj1+ neurons in 20%, and S-100+ glia in 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Neurospherederived SMA + cells have been described by other groups using similar culture methods 20,37 and may represent either greater differentiation potential of the neurosphere progenitor cells or incomplete purification of the culture. Although the organization of these mesenchymal components is comparatively disorganized, this study has taken the initial steps to demonstrate that OU contain essential elements for mesenchymal regeneration, including neural elements.…”
Section: Discussionmentioning
confidence: 99%